1994
DOI: 10.1080/00050069408257335
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of performance anxiety in music students

Abstract: M any music students experience considerable anxiety when they perform. The present article describes a two-session hypnotherapeutic approach combining relaxation, positive suggestion, and symbolic success imagery designed to reduce this performance anxiety. The subjects of the study were 40 second-and third-year music students studying at a conservatoriurn of music who were paired on the basis of their Performance Anxiety Inventory scores. One member of each pair was allocated at ra.ndom to an experimental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…These authors demonstrated differences in co-ordination patterns suggesting less efficient movements in high-anxiety conditions. Obviously, insight into the relation between anxiety and movement behaviour may have implications for designing techniques to control anxiety in order to optimize performance on perceptual-motor skills in several domains such as sports (e.g., Gould & Udry, 1994), dance (e.g., Wilson, 2002), making music (e.g., Stanton, 1994), police work (e.g., Anderson, Litzenberger, & Plecas, 2002;Le Scanff & Taugis, 2002), work of fire fighters (e.g., Ryan, Ployhart, Greguras, & Schmit, 1998), and armed forces (e.g., Arthur, Young, Jordan, & Shebilske, 1996).…”
mentioning
confidence: 99%
“…These authors demonstrated differences in co-ordination patterns suggesting less efficient movements in high-anxiety conditions. Obviously, insight into the relation between anxiety and movement behaviour may have implications for designing techniques to control anxiety in order to optimize performance on perceptual-motor skills in several domains such as sports (e.g., Gould & Udry, 1994), dance (e.g., Wilson, 2002), making music (e.g., Stanton, 1994), police work (e.g., Anderson, Litzenberger, & Plecas, 2002;Le Scanff & Taugis, 2002), work of fire fighters (e.g., Ryan, Ployhart, Greguras, & Schmit, 1998), and armed forces (e.g., Arthur, Young, Jordan, & Shebilske, 1996).…”
mentioning
confidence: 99%
“…Those habitually comprise cognitive behavioral treatment (Kendrick et al, 1982; Harris, 1987; Nagel et al, 1989), various relaxation techniques (Sweeney and Horan, 1982; Niemann et al, 1993), pharmacological methods, such as beta blockers which reduce sympathetic activation by stress (Neftel et al, 1982; Nube and Musicobgy, 1991), or even hypnosis (Stanton, 1994). The efficacy of all these methods is debatable (Kenny, 2005).…”
Section: Distributing Control Over Time Scalesmentioning
confidence: 99%
“…The present study builds on the investigations of Feener (2005), Plummer (2007), and (Stanton, 1994). It tests MPA across three different domains -cognitive, physiological/somatic and behavioural -and draws on the three-systems model of Lang et al (1988) testing 46 advanced pianists pre, during and post solo performance focusing on cognitive anxiety.…”
Section: Existing Ch and Emdr Studies For Mpamentioning
confidence: 99%
“…Two pilot studies using hypnotherapy were conducted with musicians suffering from MPA (Plott, 1987;Stanton, 1993) and extended in a large-scale study when Stanton (1994) paired pianists according to their scores on the Performance Anxiety Inventory (PAI; Nagel, Himle, & Papsdorf, 1981). One of each pair was assigned either two sessions of hypnotherapy or to a non-treatment condition.…”
Section: Existing Ch and Emdr Studies For Mpamentioning
confidence: 99%
See 1 more Smart Citation